Impact of a digital employer-based weight loss program on individuals age 65 or older - Rogers, Renee J.; Doherty, Michael; Jones, David; Jakicic, John M.; Church, Timothy S. (Frontiers in Aging, 2024)
Introduction: Older adults are not protected from obesity which has been linked to frailty, cognitive impairment, and other aging related factors. Intensive lifestyle interventions have been shown to be effective for weight loss in older adults; however, these have typically been highly intensive and less feasible for dissemination. This analysis describes weight loss in a large-scale, commercially available, digital intervention in a sub-set older adults. Methods: Older adults (N=20, 443, males=6,238; females=14,205) between 65 to 85 years of age with overweight (43.3%) or obesity (46.7%) participated in an online, self-directed, weight loss program. Behavioral-based content was delivered through weekly video lessons within an online platform that included a weight and physical activity tracking, online community, reference library and access to coaching support. Self-reported measures at time of entry into the program were used for this analysis (demographics, height, body weight, health status). Weight was reported across weeks of engagement in the curriculum. Results: Average weight loss was -3.15 kg (95% CI: [-3.20, -3.11]) at 15.5 weeks. Weight loss was significantly greater in males -3.79 kg (95% CI: [-3.89, -3.71]) versus females (-2.87 kg [95% CI: -2.94, -2.82]) (p<0.001), with similar engagement in curriculum weeks. Percent weight loss was statically significant for all age categories (p<0.05), and self-reported health conditions (p<0.05). Discussion: Short-term weight loss was observed in older adults exposed to a low-touch, self-guided, and digital behavioral-based weight loss program. Weight loss was also observed even in the presence of various chronic health conditions. .